The Evolution of Stream Valleys in the Flint Hills - Rolfe Mandel (Symphony in the Flint Hills, 2018)
Introduction: One of my favorite books is Norman Maclean’s semi-autobiographical novel, A River Runs Through It. Maclean was fascinated with Montana’s Big Blackfoot River and streams in general, and he was masterful at weaving them into metaphors. I am also fascinated with rivers but in a different way. For the past forty years I have studied the evolution of individual stream valleys, as well as entire drainage basins, and much of my research has focused on rivers and creeks in the Flint Hills.